Encoded libraries of chemically modified peptides. (June 2015) - Heinis, Christian; Winter, Greg
Highlights: Display techniques allow the genetic encoding and screening of billions of peptides. Strategies were developed to chemically modify genetically encoded peptide libraries. Chemical modifications can introduce topological constraints or functionalities. Chemical modifications render peptides attractive for therapeutic application. Abstract : The use of powerful technologies for generating and screening DNA-encoded protein libraries has helped drive the development of proteins as pharmaceutical ligands. However the development of peptides as pharmaceutical ligands has been more limited. Although encoded peptide libraries are typically several orders of magnitude larger than classical chemical libraries, can be more readily screened, and can give rise to higher affinity ligands, their use as pharmaceutical ligands is limited by their intrinsic properties. Two of the intrinsic limitations include the rotational flexibility of the peptide backbone and the limited number (20) of natural amino acids. However these limitations can be overcome by use of chemical modification. For example, the libraries can be modified to introduce topological constraints such as cyclization linkers, or to introduce new chemical entities such as small molecule ligands, fluorophores and photo-switchable compounds. This article reviews the chemistry involved, the properties of the peptide ligands, and the new opportunities offered by chemical modification of DNA-encoded peptide libraries.